Mechanical fastening, joining, and assembly - Speck, James A., 1948- (CRC Press, Taylor & Francis Group, 2015)
Mechanical Fastening, Joining, and Assembly offers practical information for understanding how fasteners and fastening systems work as well as how these products and systems are manufactured. This book provides the knowledge and tools necessary to increase fastening system performance and reliability. This second edition also explores changes that have occurred in the practice of fastening and joining. New material includes joint efficiency, creativity and innovation in fastener applications, engineering dynamics, corrosion resistant materials, thermodynamics, an overview of statics, and numerical methods.